Terror goes online [cyberterrorism]. - Cherry, S. (IEEE spectrum)
According to the book entitled "Terror on the Internet: The New Arena, the New Challenges" by Gabriel Weimann, the threat of cyberterrorism may be overstated. Weimann says the odds of a terrorist using the virtual world to attack key physical infrastructure are remote and critical networks are inaccessible from the Internet. Terrorists, however, are using the Internet to search for information about transportation, infrastructure, maps, shipping activity, economic data and even counterterrorism measures. They also use the Internet for fundraising and recruitment as well as getting their message across without censorship unlike traditional media.